Relationship Orientation, Justice Perception, and Opportunistic Behavior in PPP Projects: An Empirical Study From China - Feng, Guoli; Hao, Shengyue; Li, Xiaoguang (Frontiers in Psychology, 2021)
An equal and high-quality partnership between public and private sectors is essential to the sustainable development of public–private partnership (PPP) projects. However, in the special social circumstance in China, the public sector has a strong voice in PPP projects. According to the existing research on PPP project failure, the government's dishonest performance and negative cooperative attitude and the private sector's speculative behavior of concealing information will lead to termination or even failure of project. The attitude and behavior that reflect the relationship orientation of public sector may determine whether the private sector adopts an opportunistic behavior. However, few studies have revealed the mechanism of relationship orientation on opportunism in PPP projects. This paper proposes the connotation of the public sector's relationship orientation and designs a measurement scale from three aspects: emotional relationship orientation, instrumental relationship orientation, and rent-seeking relationship orientation. Based on the data from large construction enterprises, financial institutions and investors, and scholars with practical experience in PPP projects, this paper explores the mechanism of the public sector's relationship orientation on the private sector's justice perception and opportunistic behavior by using the structural equation model (SEM). The results show that the public sector's relationship orientation significantly affects the formation and development of the private sector's justice perception and opportunistic behavior, justice perception plays a mediating role in the process of relationship orientation acting on opportunistic behavior, and the instrumental relationship orientation is more conducive to reducing the opportunistic behavior. The results provide new ideas for changing the public sector's concept and attitude and regulating behavior in PPP projects.